Capital Markets in Emerging Economies: A Case Study of the Nairobi Stock Exchange - Kibuthu, Grace Wambui (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Over the past two decades, capital markets in developing countries have experienced a rapid evolution. The aggregate market capitalization of countries classified by the IFC as emerging markets rose from $488 billion in 1988 to $2,225 billion in 1996. Trading on these stock markets rose in similar magnitude, growing from $411 billion to $1,586 billion in that period. International donors, governments in developed countries and international financial institutions seem to pay more attention to the Asian and Latin American emerging capital markets in contrast to the African markets (particularly in Sub-Saharan Africa) as evidenced by few studies and literature on the development of capital markets in Sub-Saharan Africa. This study will, therefore, focus on capital market development in Africa, with the Nairobi Stock Exchange (NSE) as a case study. The NSE has continued to increase in importance in economic growth and capital market development in Kenya and the East Africa region. The study will, therefore, explore the path of its development with an emphasis on its structure and organization; rules, regulations and practice; trend in market performance; recent developments; challenges to development; and the way forward in the new millennium. The lessons from this study as well as the recommendations for the future will contribute to the understanding of the development of other capital markets in Africa and other developing regions of the world.